Digital Health and Wireless Solutions (Springer Nature, 2024)
This two-volume set constitutes the refereed proceedings of the First Nordic Conference on , Digital Health and Wireless Solutions, NCDHWS 2024, held in Oulu, Finland, during May 7–8, 2024. The 51 full papers included in this book together with 7 short papers were carefully reviewed and selected from 100 submissions. They were organized in topical sections as follows: Part I: Remote Care and Health Connectivity Architectures in 6G Era.- User Experience and Citizen Data.- Digitalization in Health Education.- Digital Health Innovations.- Digital Care Pathways. Part II: Clinical Decision Support and Medical AI.- Digital Care Pathways.- Novel Sensors and Bioinformatics.- Health Technology Assessment and Impact Evaluation.- Wireless Technologies and Medical Devices. This book is open access.